Isolation sound mixer - SHI SHENGXIANG (2021)
The utility model discloses an isolation audio mixer which comprises an isolation audio mixer body, and the isolation audio mixer body comprises an audio input interface connected with an audio generation module, an isolation transformation module, an audio mixing module, a control module and an audio output interface connected with an audio playing module. At least one of the audio input interface and the audio output interface is selected, and the audio generation module, the audio input interface, the isolation transformation module, the audio mixing module, the control module, the audio output interface and the audio playing module form an audio transmission line. According to the technical scheme of the utility model, the problem that all input audio signals are equipotential and output after being mixed is solved, the cost is lower, and the adaptability and compatibility are higher. 本实用新型公开一种隔离混音器，包括隔离混音器本体，所述隔离混音器本体包括与音频产生模块连接的音频输入接口、隔离变压模块、混音模块、控制模块和与音频播放模块连接的音频输出接口；所述音频输入接口和所述音频输出接口选用至少一个，并且所述音频产生模块、